Comparing drug-related hospital morbidity following heroin dependence treatment with methadone maintenance or naltrexone implantation - Ngo, H.; Tait, Robert; Hulse, G. (American Medical Association, 2008)
Context: Most research on heroin dependence treatments assesses short-term changes in patients' self-reported drug use. To our knowledge, long-term sustainability of changes in patients' drug use and associated hospital morbidity posttreatment have not been studied. Objectives: To evaluate drug-related hospital morbidity in heroin users at 6 months and 31/2 years after receiving naltrexone implant treatment and to compare these results with outcomes from a similar cohort treated with methadone maintenance treatment. Design: Retrospective longitudinal follow-up, using data prospectively collected via a state hospital (public and private) reporting system. Setting: Perth, Western Australia. Methadone maintenance dosage was generally dispensed daily by registered community pharmacies. Naltrexone implant treatment was performed as a day procedure at a community clinic. Participants: A total of 522 and 314 heroin-dependent persons (according to DSM-IV), first time treated with methadone maintenance or a naltrexone implant, respectively, between January 1, 2001, and December 30, 2002, were identified, using health record linkage. Main Outcome Measures: Planned outcomes included crude hospital admission rates, adjusted changes in risks (odds ratio [OR]), and rates (rate ratio) of "overdose-related" and "non-overdose-related" hospital morbidity associated with opioid vs nonopioid drugs 6 months and 31/2 years posttreatment. Results: Following naltrexone implant treatment, opioid-related risk decreased for overdose (OR, 0.23; 95% confidence interval [CI], 0.11-0.48) and nonoverdose (OR, 0.64; 95% CI, 0.46-0.89) conditions at 31/2 years. Such reductions were not observed after methadone treatment. Overdose on nonopioid drugs increased in older patients to 6 months: OR of 16.31 (95% CI, 3.07-86.53) for naltrexone and OR of 5.03 (95%CI, 1.18-21.54) for methadone. Nonoverdose (eg, dependence and withdrawal) associated with nonopioid drugs also increased for patients receiving the naltrexone implant: OR of 1.52 (95% CI, 1.04-2.23) at 31/2 years. In addition, there were 6 drug-related deaths: 5 after methadone maintenance and 1 after naltrexone implantation. Conclusions: Naltrexone implants, but not methadone maintenance, has long-term benefits in reducing opioid-related hospital morbidity. However, long-lasting and increased nonopioid drug-related morbidity following naltrexone implantation is particularly concerning. Similar studies are required to confirm these findings. ©2008 American Medical Association. All rights reserved.